Application of a Novel Endpoint Staging Framework: Proof of Concept in the AMBAR Study - Podger, Lauren; Stewart, Walter F.; Serrano, Daniel; Lipton, Richard B.; Gomez-Ulloa, David; Ayasse, Nicolai D.; Barnes, Frederick B.; Davis, E. Anne; Runken, M. Chris (Journal of Alzheimer's disease, 2024)
Background: A theoretical endpoint staging framework was previously developed and published, aligning outcomes (i.e., memory) to the stage of Alzheimer’s disease (AD) in which a given outcome is most relevant (i.e., has the greatest risk of degradation). The framework guides the selection of endpoints measuring outcomes relevant within a target AD population. Here, a proof of concept is presented via post-hoc analyses of the Alzheimer Management by Albumin Replacement (AMBAR) Phase 2b clinical trial in patients with AD (NCT01561053, 2012). Objective: To evaluate whether aligning endpoints measuring cognition, function, and quality of life to hypothesized ‘target’ stages of AD yields magnitudes of treatment efficacy greater than those reported in the AMBAR full analysis set (FAS). Methods: Three endpoints were tested: ADAS-Cog 12, ADCS-ADL, and QoL-AD. The magnitude of treatment efficacy was hypothesized to be maximized in the target stages of mild, mild-to-moderate, and very mild AD, respectively, compared to the full analysis set (FAS) and non-target stages. Results: For ADAS-Cog 12, the magnitude of treatment efficacy was largest in the non-target stage (–4.0, p = 0.0760) compared to target stage and FAS. For ADCS-ADL and QoL-AD, the magnitude of treatment efficacy was largest in the target stage (14.2, p = 0.0003; 2.4, p < 0.0001, respectively) compared to non-target stage and FAS. Conclusions: Findings indicated that evaluating endpoints in the most relevant AD stage can increase the magnitude of the observed treatment efficacy. Evidence provides preliminary proof of concept for the endpoint staging framework.